Competitive analysis on Indonesian reptile industry based on porter 5 forces - Nasution, Rifky Alfin Aurora; Lantu, Donald Crestofel (Journal of Business and Management, 2020)
Reptile hobbies in Indonesia's growth more significant from time to time. According to Tribunnews.com, the potency of the pet industry in Indonesia could grow to 7,1 % in 2020. With the dynamic and broad market, how is the industry competitive level based on Porter Five Forces analysis and what strategy needs to enter and survive in the industry? Respondents in this study are experts that already in the industry for more than 3 years and have profits more than IDR 10,000,000,- . All of the factors obtained through the respondent will be linked to five Porter Forces theory. The result shows that 4 out of 5 of the forces is high, so it can be concluded that the competitiveness level on Indonesian reptile industry is high. The strategy is obtained from some factors that affecting the forces level on Porter five forces analysis, by linked to SWOT analysis, and reviewed with Porter generic strategy, Focus Differentiation strategy is chosen as the best strategy to enter and survive in the market. This study has a goal to find the best strategy to enter the industry. Hopefully, by seeing this study, entrants can gain a higher rate of succession on the Indonesian reptile industry.